Keanekaragaman Dan Dominansi Pohon Penyusun Hutan Lindung Di Pulau Marsegu Kabupaten Seram Bagian Barat - Stelita Rosita Latumahina; Deli Wakano; Dece Elisabeth Sahertian (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
Maluku is known as an archipelago and has high biodiversity. One of the many islands in Maluku that has biological natural resources is Marsegu Island in the West Seram district. Marsegu Island has a very high diversity of marine resources, various types of birds and various vegetation diversity of trees. The diversity of trees in vegetation shows a variety of compositions, both variations in shape, structure or morphology, color, number, and other characteristics of plants in an area. Tree vegetation is the main constituent of forest areas and has an important function in water management, germplasm reserves, life support, development resources and sources of foreign exchange. This study aims to determine the diversity and dominance of protected forest trees on Marsegu Island, West Seram district. The method used in this research is the belt transect method. Furthermore, the tree species were identified based on the identification book. Data were analyzed using the diversity index formula from Shannon-Wienner and Simpson dominance index. The results of research conducted in the eastern and western parts of Marsegu Island found 22 species of trees as the protected forest on Marsegu Island. The Diversity Index at both stations is in the medium category with the results obtained that the east station is 2.2652 while the west station is 2.3761 and is in a stable condition, while the Dominance Index at both stations is low with the results obtained that the eastern station is 0.1618 while the west 0.1135 and no species dominates.